Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let's say I have the following:

$u=t^4+2t$

$\frac{du}{dt} = 4t^3+2$

$du = (4t^3+2)dt$

Now, if I wanted to write this in functional notation:

$f(t) = t^4+2t$

$f'(t) = 4t^3+2$

What is the next step in functional notation?

share|improve this question
1  
$\frac{du}{dt}=f'(t)\implies du=f'(t)dt$ :) –  Jonas Meyer Jan 4 '12 at 5:20
1  
It really depends on what you mean by your original third line. Maybe try $f(t+h) - f(t) = ( 4 t^3 + 2) h + O(h^2)$? –  Scaramouche Jan 4 '12 at 5:21
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Browse other questions tagged or ask your own question.